Six-year experience of detection and investigation of possible Middle East Respiratory Syndrome coronavirus cases, England, 2012-2018 - Zhao, H; ParryFord, F; Dabrera, G; Sinnathamby, M; Ellis, J; Dunning, WJ; Osman, H; Machin, N; Pebody, R (Elsevier, 2020)
Objectives Surveillance for Middle East Respiratory Syndrome (MERS) has been undertaken in the UK since September 2012. This study describes the surveillance outcomes in England from 2012 to 2018.